ESTHETIC REHABILITATION WITH IMPLANTS-SUPPORTED FIXED DENTURES AFTER PERIODONTITIS - Mihaela Mitrea; Simona Niculescu; Allia Dmor; Walid Edlibi Al Hage; Claudia Florea; Iulia Cătălina Săveanu; Carina Balcos; Norina Consuela Forna (Romanian Society of Oral Rehabilitation, 2021)
The major challenge in prosthodontics is restoring the function while maintaining the esthetics, especially considering the cases of full mounth rehabilitation. The use of a complete denture was thought to be the best solution in the past for these conditions but the perfect fit of the dentures raised questions in many cases. The advent of implants in dentistry proved tobe a boon for such patients. Dental implants are one of the most prefffered treatment options for such cases as they help to support and retain the fixed or removable prosthesis. Implant-supported prosthesis gives an opportunity to such patients to lead a normal and healthy considering their functional and esthetic demands. The success of implant osseointegration depends on both the surgeons experience and the patients anatomical-clinical and general characteristics. Therefore, only a well-trained team made up of an implantologist, a prosthetist in close contact with the patients wishes and his degree of acceptance can lead to the success of the implant-prosthetic treatment